Pengaruh Motivasi Belajar Terhadap Kemampuan Membaca Pemahaman Mahasiswa STBA-PIA Semester 5 - Hualangi, Cynthia; Effendy, Jonathan (Journal of Language, Literature and Teaching, 2019)
The aim of this research was to find whether learning motivation had a significant effect on the 5th semester of STBA-PIA students’ reading comprehension in Mandarin. This research applied ex post facto design and random sampling. The population of this study was 170 students majoring in Chinese Literature at STBA-PIA in academic year 2013/2014. The sample was 50 students. The data was collected by using questionnaire to find their learning motivation and HSK 5 test. The data was analysed by using validity test, reliability test, data description and ttest. This study showed that tcount was 7.674 and ttable (dk=48) was 1.67. The tcount bigger ttable (7.674 biger 1.67) which showed that there was a significant effect of learning motivation on the 5th semester STBA-PIA students’ reading comprehension in which the significant level was 5%. Ha was accepted while Ho was rejected.